Sviluppo e prospettive dell’industria 4.0 in italia e ruolo strategico del credito - Bottoncini, Angela; Pasetto, Attilio; Rotondi, Zeno (Argomenti, 2016)
In this paper we have tried to describe the main challenges and opportunities that the transition to the fourth industrial revolution involves, focusing on the impact on business models and supply chains. As shown by some surveys, almost all Italian companies are still unprepared to face the new challenge and are likely to start with a severe handicap compared to foreign competitors. The banks, that are the main source of financing for Italian firms, have to play a very important role in this historic transition. However, the European comparison shows that the financing of Italian corporate companies absorbs more bank capital than corporate companies of other European countries, like Germany. Then it’s important to strengthen the government guarantees schemes, freeing capital for banks and facilitating the access to the Central Guarantee Fund even by Mid Caps (the firms from 250 to 500 employees). Even now in some European countries such as Germany the access to government guarantees schemes covers medium and large companies. The greater use of this tool is desirable both for banks and for businesses.